Rock Drilling with impregnated diamond microbits - Miller, Duncan Edmund (Centre for Materials Engineering, 2014)
A fully instrumented laboratory drilling rig was designed and used to drill a variety of rock types with impregnated diamond microbits. The rocks, selected to represent a wide range of properties, were characterised by optical petrography and by the measurement of uniaxial compressive strength and relative abrasion resistance. A computer controlled electronic data logging system was used to record the power consumption, the rotational velocity, the bit thrust, the torque and the penetration rate. Tests were conducted under set thrust and under set rate of advance conditions to determine the effect of varying the bit pressure, rotational velocity, diamond mesh size and concentration, and rock type on the dependent drilling variables of diamond wear, bit wear, rock fracture, torque, power consumption, penetration rate and reactive load. The drilling efficiency was monitored by calculating the specific energy of drilling from the power consumption corrected for the power losses in the machine and from the generated torque, the latter being more sensitive. The diamond wear on a used bit was evaluated under the optical microscope by classifying each exposed stone into one of ten wear categories. The rock fracture was evaluated by scanning electron microscopy of the drilled surfaces, and by particle size distribution analysis of the drilling detritus. On the basis of the results a performance model for impregnated diamond bit drilling was formulated in which a critical stress threshold per actively drilling diamond must be exceeded for steady drilling to take place with any specific combination of bit and rock type. The optimum drilling thrust at which the specific energy is at a minimum and the penetration rate at a maximum for a given rock and bit configuration, occurs marginally above the thrust required for all the exposed diamonds to be in contact with the rock. The effective bit pressure and the rock type characteristics are crucial determinants for diamond wear type development and hence for the drilling performance within the operating range. The transition from suboptimal to optimal drilling conditions has been described in terms of the characteristic diamond wear, the specific energy, and the coefficient of friction between the bit and the rock. The mechanism of diamond wear and rock fracture are discussed with reference to the results of the optical and (ii)) scanning electron microscopy of worn diamonds and the rock detritus. It is concluded that a variety of rock properties affects the drilling performance, sometimes unpredictably and that the realistic drilling of any specific rock is necessary to determine its resistance to drilling. The necessary approach is demonstrated in detail for a single rock type, norite, for which it is shown the transition takes place at a pressure of approximately 400 MPa per actively drilling stone irrespective of the diamond size or concentration. A discussion of rock drillability testing demonstrates that experimental drilling with microbits has a valid role in the realistic evaluation of drillability and in the study of the complex fracture and wear mechanisms that must be understood for the application and rational design of appropriate bits.